Sensorineural Hearing Loss following Carbon Monoxide Poisoning - Joseph P. Pillion (Case Reports in Pediatrics)
A case study is presented of a 17-year-old male who sustained an anoxic brain injury and sensorineural hearing loss secondary to carbon monoxide poisoning. Audiological data is presented showing a slightly asymmetrical hearing loss of sensorineural origin and mild-to-severe degree for both ears. Word recognition performance was fair to poor bilaterally for speech presented at normal conversational levels in quiet. Management considerations of the hearing loss are discussed.